Measuring and Assessing Environmental, Social, and Governance (ESG) Reporting by Pakistani Listed Companies: A Capital Markets Perspective - MEMON, SHUNAID AHMED (2020)
This study is an exploratory piece of work in the nascent ESG reporting and investing market in Pakistan. The primary aim of this study is to measure and assess the ESG information provided by a sample of companies listed on the Pakistani Stock Exchange, from the perspective of an investor. Using the Borsa Sustainability Index as a model, an index was constructed which ranked the sample across multiple criteria within the pillars of Environmental, Social, and Governance (ESG) dimensions. The results of the study find considerable diversity in the ESG performance of the Pakistani companies included in the sample, however, there is a clear impetus to engage in ESG activities at the part of the managements in these companies. Using the case study method, companies evaluated for the quality of their ESG information showed that high scoring companies are likely to also have high quality ESG information. Further interrogating the value of ESG ratings through portfolio analyses found that Pakistani investors act myopically, as shown through a negative relationship between ESG ratings and stock prices, similar to the result found by studies conducted in similar institutional contexts. However, the study also shows a positive relationship between ESG rating and company accounting returns, indicating a significant management effect vis-à-vis operational decisions taken at these companies. This study provides a plethora of opportunities for future studies to be undertaken in this area, with extensions possible in the scope of the inquiry.